IMPROVEMENT OF TACTICS AND DIAGNOSTICS IN SURGICAL TREATMENT ECHINOCOCCOSIS OF THE LIVER WITH THE INTRODUCTION OF OUR DEVELOPMENT - Murod Sh. Khakimov; Sardor K. Khaitbaev; Anvar P. Rakhimov (Central Asian Journal of Medicine, 2022)
Echinococcosis is a serious medical problem in many countries of the world, where large endemic foci remain and an increase in the number of cases is observed. The disease affects almost all organs and systems of the body. Despite the improvement in the diagnosis of the disease, the frequency of unsatisfactory results of treatment and postoperative complications exceeds 20%, and mortality varies between 1-2%, depending on the nature of the course of the disease. One of the unfavorable moments is the fact that, despite the high antiparasitic efficacy of the agents used for intraoperative treatment of the residual liver cavity (ARC) (in particular, 100% glycerol), the analysis of long-term results shows that the proportion of EP recurrence has not changed much. Echinococcectomy, especially in complicated forms of the disease and giant cysts, is accompanied by suppuration of the residual cavity and the formation of bile-purulent fistulas.